(untitled) (Research, Society and Development, 2020)
Full-time education, considered as a means to obtain quality education, has been the subject of major studies and discussions in recent years in our country, due to the search for commitment to an integral education of students. The discussion around this teaching modality is due to its effectiveness in terms of teaching and learning, as well as human formation, fundamental requirements for the universalization of a quality public school. In this context, this article aims to investigate the potential and challenges of full-time school in the view of students who are linked to educational institutions that offer this modality. Through a qualitative and quantitative approach, an online questionnaire was applied to 150 students, enrolled in the three grades of high school in two full-time schools, one in Ceará State and another in Goiás State, who pointed out positive and negative aspects regarding this school modality. Through the analysis of obtained data, it was possible to infer that, even with promising results, this educational modality still inspires attention in its consolidation, given the need for a joint participation of the entire school community in order to ensure an accessible education for all. From the student perspective, the full-time school is a center of opportunities.